ANALISIS PENDAPATAN DAN POLA KONSUMSI MASYARAKAT KELURAHAN SIMPANG BARU KECAMATAN BINA WIDYA KOTA PEKANBARU PADA SAAT PANDEMI COVID-19 - Fitri Wiratanti; Sri Endang Kornita; Ando Fahda Aulia (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to analyze the income and consumption patterns of the Simpang Baru sub-district, Bina Widya District, Pekanbaru City during the covid-19 pandemic. This research is a research using primary data, while the data analyzed is that obtained using a research questionnaire with the determination of the sample using the slovin calculation as many as 382 samples. The analysis technique uses the t test or the different test with SPSS. Based on the results of the study, it is known that the income of the Simpang Baru Village Community, Bina Widya Subdistrict before the presence of covid with after the covid has decreased, this is evident from the real value of income which has decreased after the presence of covid compared to before the existence of covid19 in the Simpang Baru Village, Bina Widya District, Pekanbaru City. The pattern of consumption (expenditures) of the Simpang Baru Bina Widya Village community has changed after the covid19 was compared to before the covid19, the pattern has changed, namely before the covid the percentage of income allocation was greater for food than non-food but after the covid19 non-food expenditure was actually greater than food .